2020
DOI: 10.1001/jamacardio.2019.4528
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Change in Circulating Progenitor Cells During Exercise Stress and Risk of Adverse Cardiovascular Events in Patients With Coronary Artery Disease

Abstract: IMPORTANCE Stem and progenitor cells mobilize from the bone marrow in response to myocardial ischemia. However, the association between the change in circulating progenitor cell (CPC) counts and disease prognosis among patients with ischemia is unknown.OBJECTIVE To investigate the association between the change in CPC counts during stress testing and the risk of adverse cardiovascular events in patients with stable coronary artery disease (CAD). DESIGN, SETTING, AND PARTICIPANTSThis prospective cohort study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“… 13 , 14 In this term, inflammatory AAA which characterizes an unusually thickened aneurysm wall and dense adhesions of adjacent intra-abdominal structures represent different features from atherosclerotic AAA. 9 Although bone marrow (BM) progenitor cells contribute to the tissue inflammation and pathogenesis of cardiovascular diseases such as atherosclerotic diseases, 15 , 16 the causal role of BM-derived cells on the onset and progression of AA has not yet been fully explored. Moreover, the prevalence of AA has not been studied in MPN patients with JAK2 V617F, who are more prone to vascular disorders than both the general population and MPN patients with driver mutations other than JAK2 V617F.…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 14 In this term, inflammatory AAA which characterizes an unusually thickened aneurysm wall and dense adhesions of adjacent intra-abdominal structures represent different features from atherosclerotic AAA. 9 Although bone marrow (BM) progenitor cells contribute to the tissue inflammation and pathogenesis of cardiovascular diseases such as atherosclerotic diseases, 15 , 16 the causal role of BM-derived cells on the onset and progression of AA has not yet been fully explored. Moreover, the prevalence of AA has not been studied in MPN patients with JAK2 V617F, who are more prone to vascular disorders than both the general population and MPN patients with driver mutations other than JAK2 V617F.…”
Section: Introductionmentioning
confidence: 99%
“…Our primary finding that individuals with type 1 diabetes can mobilize HPCs and EPCs in response to exercise is of interest, as exercise-induced mobilization has been shown to be a more powerful predictor of complications and mortality than basal circulating count in thoracic surgery and coronary artery disease patients 27 , 28 , and contrasts previous research which found no mobilisation of EPCs in type 1 35 , 36 or 2 diabetes 26 . Differences between our study and those previously exploring exercise-induced mobilisation in people with type 1 diabetes likely arose due to alternative ways of quantifying circulating angiogenic cell numbers.…”
Section: Discussionmentioning
confidence: 62%
“…However, exercise-induced increases of EPCs appears attenuated in those with chronic diseases 25 , 26 , which may partially explain the increased CVD risk in these populations. Indeed, increased pre-operative exercise-induced mobilization of EPCs is correlated with reduced post-operative complications after major thoracic surgery 27 , while HPCs response to exercise was a stronger predictor of myocardial ischemia and mortality than resting circulating count in patients with coronary artery disease over a subsequent 3 year period 28 . Insight into the ability of these cells to respond to a stimulus, such as exercise, migrating into circulation and homing to ischemic tissue can be measured by the surface expression of chemokine (C-X-C motif) receptor 4 (CXCR4) and 7 (CXCR7) 29 , 30 , although evidence on the influence of type 1 diabetes is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In addition given the reduced number and function of these cells in CVD 5 , and the predictive association with mortality, it is pertinent to find therapies to augment production, mobilization and function of these cells. Exercise and physical activity has the potential to mobilize these cells into the circulation as evident from acute exercise studies showing transient increases in CPCs in both healthy 11, 24 and diseased populations 25 , although the response to acute exercise is somewhat diminished in CVD patients 26 . Long-term physical exercise and physical activity shows promise in increasing number and/or function of these CPCs 27 , potentially through promoting bone marrow production of progenitor cell subsets (although the origin of EPCs has been a topic of debate recently 28 ) or via reducing inflammatory or pro-apoptotic stimuli in the circulation 29 , thus enhancing survival of these cells in our body.…”
Section: Discussionmentioning
confidence: 99%